Magnesia doped Ag/Al2O3 - sulfur tolerant catalyst for low temperature HC-SCR of NOx - More, Pavan M.; Jagtap, Neelam; Kulal, Atul B.; Dongare, Mohan K.; Shubhangi B. Umbarkar (Applied Catalysis B-Environmental, 2014)
A series of magnesia doped Ag/Al2O3 catalysts were prepared by modified impregnation method using boehmite as alumina precursor. The prepared catalysts were characterized and tested for the SCR of NOx using propene as reductant under lean condition. Doping of magnesia improved the low temperature catalytic activity for HC-SCR of NOx as well as sulfur tolerance. Maximum 98% NO conversion with 100% selectivity for N-2 was obtained at 350 degrees C with 7% Mg doping to Ag/Al2O3. The improvement in low temperature activity and the sulfur tolerance has been correlated to decreased acidity after addition of magnesia to alumina support. In situ FTIR study showed that the deactivation in the presence of SO2 was due to the sulfation of silver and aluminum sites in Ag/Al2O3 catalyst, however its formation was suppressed in case of magnesia doped Ag/Al2O3 improving its sulfur tolerance. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: HC-SCR; Low temperature activity; NOx; Sulfur tolerance

Activation by pretreatment of Ag-Au/Al2O3 bimetallic catalyst to improve low temperature HC-SCR of NOx for lean burn engine exhaust - More, Pavan M.; Nguyen, Duy L.; Granger, Pascal; Dujardin, Christophe; Dongare, Mohan K.; Shubhangi B. Umbarkar (Applied Catalysis B-Environmental, 2015)
Bimetallic Ag-Au/Al2O3 catalyst was synthesised by successive impregnation of 1% Au and 1% Ag on in-house prepared high surface area alumina (450 m(2)/g). The corresponding monometallic catalysts were also prepared by loading 1% Ag or 1% Au on the same high surface area alumina for comparison. The catalysts were characterised by various physico-chemical techniques and tested for SCR activity under lean burn engine exhaust conditions. Ag-Au/Al2O3 catalyst prepared by successive impregnation method showed considerably higher NO reduction (100%) to N-2 compared to 1% Au/Al2O3 (70%) whereas the activity was comparable with that of 1% Ag/Al2O3 (96%). The effect of various pretreatments on SCR activity of Ag-Au/Al2O3 was studied and pretreatment at 250 degrees C in flow of hydrogen was found to give the best results with 100% NO conversion to N-2 at 353 degrees C. Further ageing of the catalyst under reaction feed at 500 degrees C resulted in considerable increase in low temperature activity of bimetallic catalyst with similar to 40% NO conversion at 222 degrees C. Even though the SCR activity of pretreated Ag-Au/Al2O3 and Ag/Al2O3 were comparable, after ageing the Ag-Au/Al2O3 showed significantly higher NO conversion (95%) compared to Ag/Al2O3 (83%) and Au/Al2O3 (70%). The formation of H-2 and CO due to steam reforming of higher hydrocarbon (decane) was evidenced at the temperature of highest deNO(x) activity. Detailed investigation of the textural properties of the pretreated and aged catalysts showed presence of well dispersed metallic Au and Ag-n(delta+) clusters after pretreatment in hydrogen at 250 degrees C. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Ag-Au bimetallic catalyst; Catalyst ageing; dispersion; Low temperature HC-SCR; Steam reforming

Rational preparation of Ag and Au bimetallic catalysts for the hydrocarbon-SCR of NOx: sequential deposition vs. coprecipitation method - More, Pavan M.; Nguyen, D. L.; Dongare, Mohan K.; Shubhangi B. Umbarkar; Nuns, N.; Girardon, J. S.; Dujardin, Christophe; Lancelot, Christine; Mamede, Anne-Sophie; Granger, P. (Applied Catalysis B-Environmental, 2015)
This study emphasizes the importance of the preparation method for bimetallic Au-Ag catalysts supported on alumina in the selective reduction of NOx by hydrocarbons with gas feed compositions representative of diesel fuelled engine exhaust gas. An optimal balance between oxidative and reductive surface properties is obtained when Au and Ag are successively introduced. Significant re-dispersion processes take place when the catalyst runs at 500 degrees C leading to a gain in activity at low temperature and ascribed to a better interaction between Au and Ag species. Co-precipitation leads to a preferential formation of intermetallic Au-Ag particles which is detrimental to the catalytic performances. Aging at 500 degrees C leads to a significant particle sintering and a strengthening of the metallic character. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Au-Ag particles; Co-precipitation; DeNO(x) reaction; HC-SCR

Template-free sol-gel synthesis of high surface area mesoporous silica based catalysts for esterification of di-carboxylic acids - More, Pavan M.; Umbarkar, Shubhangi B.; Dongare, Mohan K. (Comptes Rendus Chimie, 2016)
High surface area mesoporous silica based catalysts have been prepared by a simple hydrolysis/sol-gel process without using any organic template and hydrothermal treatment. A controlled hydrolysis of ethyl silicate-40, an industrial bulk chemical, as a silica precursor, resulted in the formation of very high surface area (719 m(2)/g) mesoporous (pore size 67 angstrom and pore volume 1.19 cc/g) silica. The formation of mesoporous silica has been correlated with the polymeric nature of the ethyl silicate-40 silica precursor which on hydrolysis and further condensation forms long chain silica species which hinders the formation of a close condensed structure thus creating larger pores resulting in the formation of high surface mesoporous silica. Ethyl silicate-40 was used further for preparing a solid acid catalyst by supporting molybdenum oxide nanoparticles on mesoporous silica by a simple hydrolysis sol gel synthesis procedure. The catalysts showed very high acidity as determined by NH3-TPD with the presence of Lewis as well as Brensted acidity. These catalysts showed very high catalytic activity for esterification: a typical acid catalyzed organic transformation of various mono- and di-carboxylic acids with a range of alcohols. The in situ formed silicomolybdic acid heteropoly-anion species during the catalytic reactions were found to be catalytically active species for these reactions. Ethyl silicate-40, an industrial bulk silica precursor, has shown a good potential for its use as a silica precursor for the preparation of mesoporous silica based heterogeneous catalysts on a larger scale at a lower cost. (C) 2016 Published by Elsevier Masson SAS on behalf of Academie des sciences.